1997
DOI: 10.1007/s004600050330
|View full text |Cite
|
Sign up to set email alerts
|

Total cross sections for electron scattering from molecules: NH3 and H2O

Abstract: By developing the semi-empirical formula recently obtained for total cross sections of electron scattering from diatomic molecules in the intermediate-and highenergy range, we calculate the total cross sections for electron scattering from molecules (NH 3 and H 2 O) over an incident energy range of 10-1000 eV. The total cross sections have also been calculated by using the complex optical potential and the additivity rule. Compared with other available experimental and calculating data, excellent agreements ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…Theoretical calculations have been reported by Manjul and Baluja [13] and Gianturco [14], and they agree well with the present results beyond 10 eV, but at lower energies these theoretical data are higher while maintaining the shape of the curve. Liu et al [16] have reported total cross sections using two formalisms: one using an additivity rule that overestimates the cross section below 100 eV as expected and another using a semiempirical formula that is lower compared to all reported data below 30 eV. Both datasets of Liu et al [16] agree well with present results beyond 200 eV.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Theoretical calculations have been reported by Manjul and Baluja [13] and Gianturco [14], and they agree well with the present results beyond 10 eV, but at lower energies these theoretical data are higher while maintaining the shape of the curve. Liu et al [16] have reported total cross sections using two formalisms: one using an additivity rule that overestimates the cross section below 100 eV as expected and another using a semiempirical formula that is lower compared to all reported data below 30 eV. Both datasets of Liu et al [16] agree well with present results beyond 200 eV.…”
Section: Resultssupporting
confidence: 80%
“…Experimental data for low impact energy have also been reported by Szmytkowski et al [22] and agree well with the present results beyond 30 eV, but below this energy the experimental data appear to be higher than calculations. In contrast the experimental data reported by Zecca et al [9] at higher energy are in good agreement [15]; violet dashed-dot line, theoretical data of Liu et al using ADR method [16]; brown dashed-dot-dot line, theoretical data of Liu et al using SEF method [16]; cyan dotted line, theoretical data of Munjal and Baluja [13] using ADR method; dark yellow short dash-dot line, Theoretical data of Gianturco [14].…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…Jain [33] PHYSICAL REVIEW LETTERS 123, 033401 (2019) 033401-2 spherical complex optical potentials to compute σ T over the energy range of 10-3000 eV, recommending the SEP(CP) a1 model below 100 eV. Liu et al [35] employed a semiempirical formula as well as the complex optical potential and the additivity rule to calculate σ T over an incident energy range of 10-1000 eV, the former being closer to experiment. Okamoto et al [34] calculated vibrational elastic integral and differential cross sections using an ab initio static potential and approximate electron exchange and target polarization.…”
mentioning
confidence: 99%